Analyzing how population size, GRDP growth, and workforce size impact the unemployment rate in Jember Regency - Setiawan, I Made Kusuma Yudha; Marseto, Marseto (Jurnal Riset Multidisiplin dan Inovasi Teknologi, 2024)
The purpose of this research is to evaluate the relationship between the Population, Gross Regional Domestic Product (GRDP), and Workforce Size with the unemployment rate in Jember Regency. This study uses secondary data in the form of time series data collected from the Central Statistics Agency of Jember Regency from 2008 to 2023. The analytical methods used include descriptive statistical analysis and multiple linear regression. Hypothesis testing includes partial tests (t-tests), simultaneous tests (F-tests), and the coefficient of determination (R2). Additionally, classical assumption tests are conducted, which consist of normality, multicollinearity, heteroscedasticity, and autocorrelation tests. The results of this study indicate that the variables of Population, GRDP, and Workforce Size have a positive and significant effect on the unemployment rate in Jember Regency.